2010
DOI: 10.1002/jmr.1035
|View full text |Cite
|
Sign up to set email alerts
|

Proteolysis activity of IgM antibodies from rheumatoid arthritis patients' sera: evidence of atypical catalytic site

Abstract: The IgM antibodies from rheumatoid arthritis (RA) patients' sera were screened for peptide hydrolyzing activity. Recovery of structurally intact IgM antibodies (Abs), in a single step, was achieved using a weak anion-exchange methacrylate monolith disk. The IgM Abs from patients' sera hydrolyzed the Pro-Phe-Arg-4-methyl-coumaryl-7-amide (PFR-MCA) substrate appreciably compared to the healthy donors. The apparent K m values of IgM Abs from patients' sera were between 0.4 and 0.7 mM. Furthermore, IgM Abs display… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0
2

Year Published

2012
2012
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 28 publications
0
10
0
2
Order By: Relevance
“…The high selectivity and extension to a wide variety of ligand chemistry with CIM media have gained attention in the area of bio separation [35]. There are already several reports on purification of macromolecules like DNA, RNA, viruses like particles, IgM, IgG and enzymes using CIM ion exchange systems [35][36][37][38][39][40]. In our study, we used a CIM-CM disk for the purification of uricase enzyme.…”
Section: Discussionmentioning
confidence: 96%
“…The high selectivity and extension to a wide variety of ligand chemistry with CIM media have gained attention in the area of bio separation [35]. There are already several reports on purification of macromolecules like DNA, RNA, viruses like particles, IgM, IgG and enzymes using CIM ion exchange systems [35][36][37][38][39][40]. In our study, we used a CIM-CM disk for the purification of uricase enzyme.…”
Section: Discussionmentioning
confidence: 96%
“…Polyclonal antibody studies indicated that the average catalytic activity of IgMs far exceeds that of IgGs (15,19,35). IgGs develop from IgMs by a switch of C-domain gene usage, usually accompanied by immunogen-driven adaptive accumulation of V-domain mutations.…”
Section: Discussionmentioning
confidence: 99%
“…The same conclusion may be reached from the substrate classes sensitive to catalytic antibodies that are produced constitutively with no requirement for exposure to an external immunogen. Very small peptide "microantigens"' are hydrolyzed by antibody V-domains without the involvement of traditional high affinity noncovalent binding interactions that are developed adaptively by immunogen-driven B cell clonal selection (14,15). The same hydrolytic reaction is catalyzed frequently by Bence Jones proteins, light chains produced by multiple myeloma patients (16,17).…”
mentioning
confidence: 99%
“…Встановлено, що 7 із 8 препаратів IgGантитіл сироватки крові хворих на ревматоїдний артрит Ревматоїдний артрит -це системне за-хворювання сполучної тканини з переваж-ним ураженням дрібних суглобів за типом ерозійнодеструктивного поліартриту неясної етіології зі складним автоімунним патогене-зом. Нещодавно в сироватці крові хворих на ревматоїдний артрит було виявлено IgG і IgM антитіла, здатні гідролізувати синтетичний пептид ProPheArg4метилкумаринімід [34]. При цьому пептидазна активність IgMантитіл була на порядок вищою, ніж активність IgG антитіл.…”
Section: рис 1 дот-блот-(A) і вестерн-блот-аналіз (б) антигенної спunclassified
“…дані про те, що у сироватці крові людей із сеп-сисом міститься високий рівень протеолітично активних IgGантитіл, здатних гідролізувати, подібно до IgMантитіл сироватки крові хворих на ревматоїдний артрит [34], синтетичний пеп-тид ProPheArg4метилкумаринімід [35,36]. При цьому титр протабзимів і рівень їхньої каталітичної активності позитивно корелює зі…”
Section: рис 5 протеолітична активність щодо загальних гістонів тимunclassified